Variation in soil C and microbial functions across tree canopy projection and open grassland microenvironments - Lai, Roberto; Lagomarsino, Alessandra; Ledda, Luigi; Roggero, Pier Paolo (TURKISH JOURNAL OF AGRICULTURE AND FORESTRY, 2014)
Mixtures of grasslands and perennial woody crops or vineyards represent a major source of potential carbon storage or release. Understanding the spatial variability of soil properties in these ecosystems is important in determining soil constraints related to the management of soil resources. The aims of the study were 1) to explore the spatial variability associated to the trees for soil C storage and its components and reactivity; and 2) to assess the similarities between microenvironments in terms of microbial functional diversity. Eight microenvironments characterized by different long-term soil management practices and different positions with respect to woody plant canopy soil vertical projections were selected in a Mediterranean agropastoral system. Four management types were considered: pasture, hay crop, grass-covered vineyard, and tilled vineyard. Soil organic C, microbial biomass, and respiration were measured to assess C storage and dynamics, while functional diversity was determined by means of soil enzyme activities. The results showed that the microenvironmental variation of soil organic C and functional microbial diversity generated by the tree canopies in the wooded grassland can be very relevant for an accurate assessment of soil organic C content and its dynamics. The same was not applicable to vineyards, where the spatial variation of both soil organic C and functional diversity was negligible, independently of the soil management practices. These results suggest that in such systems the microscale spatial variability generated by the trees is worth of further investigation for improving our understanding of the long-term management effects on soil C dynamics.
Keywords: agroforestry systems; carbon mineralization; Enzyme activity; long-term management; Tree effect; vineyards